Handing-over Notes Bamenda Division from Dr. M. D. W. Jeffreys, Snr. Dist. Officer to I. F. W. Schofield, Esq. District Officer (Colonial Letters and the Contact of Knowledges, 1939)
This file contains colonial handing over notes from Jeffreys
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies